Simmel no Brasil - Leopoldo Waizbort (Universidade do Estado do Rio de Janeiro, 2007)
Simmel's presence in the social sciences in Brazil is varied and longstanding. This article attempts to indicate some of the forms of appropriation, reception, and importation of his ideas and writings, visiting various Brazilian social scientists who are in some way considered illustrative of the underlying questions and seeking to demonstrate the multiplicity of forms and modes of relations they establish with Simmel's work. From this point of view, the research allows tracing a history of sociology in Brazil.